Considerazioni sulla receptio legis alla luce del m.p. Mitis Iudex Dominus Iesus (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Osservazioni preliminari sul concetto di receptio legis - 2. Fondamenti giustificativi della receptio legis nell’ordinamento ecclesiale - 3. Valore giuridico della receptio legis. Effetti e criteri - 4. La recezione del m.p. Mitis Iudex Dominus Iesus. Soggetti, condizioni, forme - 5. Note conclusive.Some considerations upon the receptio legis in the light of the m.p. Mitis Iudex Dominus IesusABSTRACT: Reception of law can be described as the process by which the recipients of a canonical law verify its reasonableness. This process appears mostly in the material observance of the law. The essay examines firstly the theological and ecclesiological legitimacy of reception, and then it explores which are its effects upon the binding force of the law and when they occur. Finally, it tries to employ this concept in describing the way in which the m.p. Mitis Iudex has been accepted and implemented in some local Churches.